INSTITUTING FUNDAMENTAL RIGHTS ACTIONS IN NIGERIA: UNRESOLVED ISSUES - Chijioke, Collins Obioma; Toby, Boma Geoffrey (PEOPLE: International Journal of Social Sciences, 2020)
Instituting fundamental Right actions has become one of the most popular forms of litigations in Nigeria; and for this credit must be given to the very liberal Fundamental Rights (Enforcement Procedure) Rules, 2009 (FREP RULES) as against the FREP Rules, 1979 which is repealed. One cannot boldly say, without fear of contradiction that our courts are as proactive in their approach to some basic issues in fundamental rights litigation as the FREP Rules intend. This paper set out to re-visit the issue of jurisdiction in respect of fundamental rights litigations and the required number of applicants permitted to institute such actions; reviewing some authorities in the course and finally resolving that there is a need for the apex court to finally distinguish between its decisions in Turku v. Government of Gongola State (1988) All NLR 42 and Grace Jack v. University of Agriculture Makurdi (2004) LPELR – 1587 SC, (2004); 5NWLR (Pt. 865) 208 and to pronounce on the issue of the number of applicants that may present fundamental rights’ cause in court; at any time it is called upon to do so. The paper also recommended in the alternative, tinkering of the FREP Rules to specifically handle the issues.